2009
DOI: 10.1111/j.1477-2574.2009.00043.x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous pancreatectomy and liver transplantation: a single-institution experience

Abstract: We report a series of pancreatectomy or pancreaticoduodenectomy and simultaneous LT in patients with extensive malignancy or impending liver failure that prevented pancreatectomy. This series provides evidence that combined pancreatic resection and LT can be a strategy in both radical resections and cases with ESLD that would otherwise preclude operative intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…One patient in our series had prior liver transplantation for primary sclerosing cholangitis. Wu et al reported no signs of tumor recurrence in their patients at 79-to 145month follow-up (36). In the current literature, the early results after liver transplantation for cholangiocarcinoma are disappointing.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…One patient in our series had prior liver transplantation for primary sclerosing cholangitis. Wu et al reported no signs of tumor recurrence in their patients at 79-to 145month follow-up (36). In the current literature, the early results after liver transplantation for cholangiocarcinoma are disappointing.…”
Section: Discussionmentioning
confidence: 95%
“…Progression of the primary tumor in malignant cases remains the most common cause of mortality, which emphasizes the important role of patient selection in predicting successful long-term outcomes. Although this is a major undertaking in an immunosuppressed patient, data from small series and case reports have suggested it is feasible and is associated with good long-term results, including the one published by our center in 2009 (33)(34)(35)(36). He subsequently underwent pancreaticoduodenectomy for a pancreatic head lesion that was proven to be distal cholangiocarcinoma.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…To our knowledge, only 9 other cases of liver transplantation for IPN have been reported in the literature. [7][8][9][10][11][12][13][14][15] With our case, there are now 2 reported recurrences of the disease in the native biliary tree left in place during surgery. 15 Both patients died from that relapse.…”
mentioning
confidence: 93%
“…On the other hand, all patients who underwent pancreaticoduodenectomy concomitantly with OLT remained alive after follow-up periods of 22, 18, and 24 months, respectively. 8,10,14 As for neoplasia, 2 of the 3 cases with frank invasive carcinoma according to the final pathology results died within a few months of OLT. 13,15 On the other hand, 3 of the 4 cases reported to have moderate-to high-grade dysplasia or CIS according to the final pathology results were well and alive 15 months, 18 months, and 16 years, respectively, after OLT.…”
mentioning
confidence: 99%